2001
DOI: 10.1128/jvi.75.20.9925-9938.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Membrane-Binding Ability of the C-Terminal Cytoplasmic Domain of Human Immunodeficiency Virus Type 1 Envelope Transmembrane Protein gp41

Abstract: The amphipathic ␣-helices located in the cytoplasmic tail of the envelope (Env) transmembrane glycoprotein gp41 of human immunodeficiency virus type 1 have been implicated in membrane association and cytopathicity. Deletion of the last 12 amino acids in the C terminus of this domain severely impairs infectivity. However, the nature of the involvement of the cytoplasmic tail in Env-membrane interactions in cells and the molecular basis for the defect in infectivity of this mutant virus are still poorly understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 72 publications
3
52
0
Order By: Relevance
“…Inhibition of the protease activity encoded in the virus prevents the cleavage of p55 and has been shown to regulate fusion (22,23). Studies with peptides derived from two α helical "lentivirus lytic peptide" domains (LLP-1 and LLP-2) that are highly conserved in HIV-1 have suggested that these domains strongly interact with the cytoplasmic leaflet of plasma membrane (47)(48)(49)(50). The INA-labeling data presented in this study are consistent with this model (Figures 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the protease activity encoded in the virus prevents the cleavage of p55 and has been shown to regulate fusion (22,23). Studies with peptides derived from two α helical "lentivirus lytic peptide" domains (LLP-1 and LLP-2) that are highly conserved in HIV-1 have suggested that these domains strongly interact with the cytoplasmic leaflet of plasma membrane (47)(48)(49)(50). The INA-labeling data presented in this study are consistent with this model (Figures 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…The three highly conserved amphipathic ␣-helical segments, designated lentiviral lytic peptide 1 (LLP)-1, LLP-2, and LLP-3, located in the C terminus of the cytoplasmic tail are thought to be associated with the inner surfaces of viral and cellular membranes (33,45). We previously showed that the multimerization potential and membrane binding ability of the cytoplasmic tail may play a crucial role in virus replication (3,5,7,28) and that the N-terminal segment of LLP-1 contains a structural determinant critical for modulating Env stability (27).…”
mentioning
confidence: 99%
“…The HIV-1 gp41 CT consists of the "Kennedy" polypeptide sequence (aa 731-752) and the lentivirus lytic peptide (LLP1-2, aa 773-862), which contains three highly conserved ␣-helix domains as follows: LLP1 (aa 833-862), LLP2 (aa 773-793), and LLP3 (aa785-807) (11). The HIV-1 gp41 CT has many functions, including interaction with the plasma membrane, decrease of bilayer stability, alteration of membrane ionic permeability, and mediation of cell killing (10,(12)(13)(14)(15)(16). Recent studies have shown that the gp41 CTs of HIV and simian immunodeficiency virus correlate with their infectivity and Env-mediated cell-cell fusion (10,15).…”
mentioning
confidence: 99%